(tan^2a/cos^2b)-(sec^2a/cot^b)=?
Answers
Answered by
6
= (tan^2a/cos^2b) - (sec^2a/cot^2b)
= sin^2a/cos^2a/cos^2b - 1/cos^2b/cos^2b/sin^2b
= sin^2a/cos^2a cos^2b - sin^2b/cos^2acos^2b
= sin^2a-sin^2b/cos^2a cos^2b
= cos^2b - cos^2a/cos^2a cos^2b
= sec^2a - sec^2b.
Hope this helps!
= sin^2a/cos^2a/cos^2b - 1/cos^2b/cos^2b/sin^2b
= sin^2a/cos^2a cos^2b - sin^2b/cos^2acos^2b
= sin^2a-sin^2b/cos^2a cos^2b
= cos^2b - cos^2a/cos^2a cos^2b
= sec^2a - sec^2b.
Hope this helps!
siddhartharao77:
Thank You Avinash for the brainliest
Similar questions